Structural decomposition analysis applied to the energy use in Poland - Paulina Stachura (Economic and Environmental Studies (E&ES), 2018)
To understand historical changes in energy performance of economy or specific sector, it is useful to evaluate the driving forces underlying these changes. Structural decomposition analysis allows identifying the impact of the external factors, such as technological, demand, and demographic effects on the fluctuations of the total energy use, CO2 emissions, and other socio-economic indicators. This study applies methods of structural decomposition analysis to determine relative prominence of diverse sources of changes in the energy use in the Polish economy and its main sectors between 2000-2015. The author presents the methodology of decomposition into different explanatory factors, among which energy savings based on top-down indicators, which allows showing additionally what the role of energy efficiency improvements is at the level of the different sub-sectors and end-uses. The analysis is extended into comparison to European statistics in the context of implementation and monitoring of the UE indicative energy targets.
Keywords: O18; Q40; Q56; 330; energy use; structural decomposition analysis; indicators; energy efficiency